KINERJA TENAGA PENGEMUDI MOTOR SAMPAH DALAM PELAYANAN PUBLIK DI KECAMATAN PAAL DUA KOTA MANADO - Richard Daniel Mantik; Michael ., Mamentu; Deysi L. N. Tampongangoy (Sam Ratulangi University, 2021)
The purpose of this study was to determine the cause of the weak performance of the Garbage Motorbike Driver in Paal Dua District. The method used in this research is descriptive with a qualitative approach. This research was conducted in Paal Dua District, Manado City using research instruments through observation and in-depth interviews to 30 respondents. From the results of the study it was found that the problem in this aspect of timeliness then had an impact on the aspects of quantity and effectiveness.In the aspects of quality, independence and work commitment it was found that there were no fundamental problems that affected the performance of garbage motorbike drivers, on aspects of quality, independence and commitment concluded that in general the drivers of garbage motorbikes in Paal Dua sub-district have strong integrity towards their work. To strengthen the performance of garbage motorbike drivers in Paal Dua sub-district, it must be strengthened or added to the aspect of good infrastructure support, in this case at the TPA, it is necessary to add heavy equipment, the availability of fuel and operators as needed